ANALISIS PENGARUH KEPUASAN DAN BRAND TRUST TERHADAP MINAT BELI ULANG PANTENE (STUDI PADA ‘YOUNG FEMALE’ SEMARANG) - Nia, Itsna Ainin; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2016)
Pantene is a shampoo well-known brand from PT. Procter & Gamble. Pantene became the market leader of category Shampoo over the last four years. But the high competition make a Brand value indexs of Pantene shampoo has decreased, which means there is a decline in the performance of the brand. It is characterized by the decline in TOM Brand, Satisfaction, and Brand Share. As a market leader Pantene need to be careful because it is an indication of decreased in repurchase Intention. This study aims to determine the effect Selebrity Endoser and quality of repurchase Intention by Brand Trust and satisfaction as an intervening variable.This study used data on 197 young female respondents aged 17-35 in the city of Semarang who had used Pantene more than twice, Thus, this study can not be generalized to the context of other studies, both gender and age. This study used six variables: Celebrity Endorser, Quality, Satisfaction, Brand Trust, and Repurchase Intention. The analysis technique used in this research is Structural Equation Model (SEM) of AMOS 22.0. Research shows that to improve repurchase intentionof Pantene to young female in Semarang can only be done through one process, namely improving the quality of Pantene that will increase satisfaction and ultimately increase Interests repurchase intention of young female in city Semarang